Rosalind Franklin y la Estructura Molecular del ADN: Un caso de historia de la ciencia para aprender sobre la naturaleza de la ciencia - Acevedo-Díaz, José Antonio; García-Carmona, Antonio (Revista Científica, 2016)
The Rosalind Franklin’s case regarding the elucidation of the molecular structure of DNA is presented as an interesting story of the history of science to address a set of questions related to the nature of science (NOS) from an explicit and reflective approach. The teaching proposal is aimed to the pre-service teachers training in NOS issues and its didactics. Attention is given to both epistemic and non-epistemic aspects in the narration and the NOS questions asked for reflecting about them. Also, some methodological recommendations for implementing the didactic proposal in science classroom are offered. This involves the follows: (i) in small groups, the students read the controversy and respond to some questions on NOS; (ii) they present their responses to the whole-class; and (iii) they revise their initial responses in light of the whole-class discussion.